Pengaruh Motivasi dan disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Lingkar Sakti Mas Banjarmasin - Siti Mardah; Citra Amelia; Saidilah (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This study aims to assess the influence of Motivation and Work Discipline on Employee Performance at PT. Lingkar Sakti Mas Banjarmasin. This study uses a quantitative approach with 32 respondents, all of whom were sampled through saturated sampling techniques. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression. The results showed that Motivation (X1) had a significant effect on Performance (Y), with a calculated t value of 2.355> t table 2.042 and a significance of 0.026 <0.05. Work Discipline (X2) also had a significant effect, with a calculated t value of 3.683> t table 2.042 and a significance of 0.001 <0.05. Simultaneous test (F test) shows F count 12.310 > F table 3.328 and significance 0.000 < 0.05, which means that together Motivation and Work Discipline have a significant effect on Performance. In conclusion, improving employee performance can be achieved if work motivation and work discipline are carried out in a balanced and consistent manner.